KAJIAN SOSIO DEMOGRAFI DAN MANAJEMEN SUMBERDAYA TERHADAP KESEJAHTERAAN EKONOMI KELUARGA DI KABUPATEN KERINCI PROVINSI JAMBI - Suandi, Suandi (Jurnal AGRISEP, 2010)
The objectives of this study are to identify and describe the level of family economic wellbeing As well as the socio-demographic and family resource management, and to analyze the influence of socio-demographic and management of resources factors on the economic well-being of family. TheStudy designwascrosssectional The study was conducted in the Kerinci regency of Jambi Province. Research time for eigth months. Research variables: (1) the family's economic well-being (objective and subjective), (2) sociodemographic (education level, skills of heads of families, and the level of dependency ratio), and (3) management of family resources (management of time, number of family members, and financial management). The research sample were 174 households or ten percent of the population (1743 households) are chosen using cluster, purposive and random sampling methods. Data were collected using survay, indepth interview, and Focus Group Discussion (FGD). Data analysis using Structural Equation Modelling (SEM) with LISREL program (version 8.7).The results showed that the level of wellbeing Families in the study area were relatively wealthy. Objective Economic well-being of expenditure proxy for Rp.10.541.000 per year. The level of satisfaction or subjective economic well-being was highly (68.4%) for daily needs. Through the SEM model testing showed that socio-demographic and family resource management variables, both directly and indirectly positive effect and significant on the level of economic well-being(objective and subjective) of the family with a value betha (ß) respectively, are 6.2 and 3.1.